Comparison of urodynamic results and quality of life between women with interstitial cystitis and overactive bladder - Chin-Chieh Hsu; Ching-Chung Liang; Shuenn-Dyh Chang; Chih-Wei Chien; Wu-Chiao Hsieh (Elsevier, 2020)
Objectives: Some symptoms of overactive bladder overlap with those of interstitial cystitis. This study was conducted to compare the urodynamic results and quality of life of patients with the two conditions. Materials and Methods: Urodynamic data were retrospectively analyzed in 55 females with interstitial cystitis and 171 females with overactive bladder between 2012 and 2016. Females with overactive bladder were divided into detrusor overactivity group and non-detursor overactivity group based on urodynamic results. All recruited patients completed validated questionnaires including incontinence impact questionnaire (IIQ-7), urogenital distress inventory (UDI-6), and short form 12 health survey (SF-12). Patient demographics, total scores of questionnaires, and urodynamic results were compared among interstitial cystitis, detrusor overactivity, and non-detrusor overactivity groups. Results: The age and body mass index of interstitial cystitis patients were significantly lower than that of overactive bladder patients. The severity of urinary symptoms was higher in interstitial cystitis group than in non-detrusor overactivity group from questionnaire, but similar as detrusor overactivity group. Interstitial cystitis group had lower maximum flow rate, lower residual urine volume, lower maximum cystometric capacity, and higher maximal urethral closure pressure compared with non-detrusor overactivity group. However, there was no significant difference in urodynamic parameters between interstitial cystitis and detrusor overactivity groups. Conclusion: Interstitial cystitis and overactive bladder have a negative impact on quality of life, but urodynamic studies are not effective in distinguishing between interstitial cystitis and detrusor overactivity. Keywords: Interstitial cystitis, Overactive bladder, Overactive detrusor, Urodynamic